Promising technical solutions for integrating Ukrainian and European railway transportation - Mokriy, T.F.; Lapina, L.G.; Sobolevska, M.B.; Horobets, D.V.; Pasichnyk, S.S. (Доповіді НАН України, 2025)
A complex of theoretical researches on solving the problems of integration of Ukrainian and European railway transport was carried out. Technical solutions have been developed to create conditions for the safe rolling stock operation on railways of Ukraine and the European Union (EU) countries, as well as for the introduction of effective freight transportation technologies. New wheel tread profiles for railway vehicles are proposed. Th e use of wheels with these profiles will ensure acceptable indicators of vehicles dynamic qualities and conditions of interaction between wheels and rails on Ukrainian and European railways. It will also reduce wheel and track wear. Th e methodology of forming disturbances acting on a railway vehicle from the track and causing its spatial vibrations has been proposed to calculate indicators of vehicle dynamic qualities. A new freight transportation technology using wagons with swap bodies has been considered for Ukraine. Recommendations on fastening elements of the swap body to the wagon undercarriage frame have been developed. Th e implementation of new technical solutions will increase the speed and safety of train motion, improve the interaction of the vehicle running gears with the track, and contribute to the creation of the modern Ukrainian railway complex and its integration into European transport networks. Проведено комплекс теоретичних досліджень щодо вирішення проблем інтеграції українського та європейського залізничного транспорту. Розроблено технічні рішення щодо створення умов для безпечної експлуатації рухомого складу на залізницях України та країн Європейського Союзу (ЄС), впровадження ефективних технологій перевезення вантажів. Запропоновано нові профілі протектора коліс залізничного транспорту. Застосування коліс із цим профілем забезпечить прийнятні показники динамічних якостей транспортних засобів та умов їх взаємодії з рейками на залізницях України та Європи. Це також зменшить знос коліс і гусениць. Для розрахунку показників динамічних якостей транспортного засобу запропоновано методику формування збурень, що діють на залізничний транспортний засіб з боку колії та спричиняють його просторові коливання. Розглянуто нову для України технологію перевезення вантажів вагонами зі змінними кузовами. Розроблено рекомендації щодо кріплення елементів змінного кузова до рами ходової частини вагона. Впровадження нових технічних рішень дасть змогу підвищити швидкість і безпеку руху поїздів, покращити взаємодію ходових частин вагона з колією, сприятиме створенню сучасного залізничного комплексу України та його інтеграції в європейські транспортні мережі.